Microbiological surveillance of operation theatre’s and intensive care units in a tertiary care hospital in NCR region, New Delhi - Singh, Soumya; Kumar, Rohit; Sarma, Mrinmoy (International Journal of Research in Medical Sciences, 2020)
Background: Harbouring of potential pathogens in operation theatres (OTs) and intensive care units (ICUs) of hospital is a major cause of patient’s morbidity and mortality. Environmental monitoring by the microbiological testing of surfaces and equipments is useful to detect changing trends of types and counts of microbial flora. High level of microbial contamination indicates the needs for periodic surveillance aimed at early detection of bacterial contamination levels and prevention of hospital acquired infections. Methods: During a period of 6 months from January 2019 to June 2019, Air sampling from Operation theaters and Intensive care units were done by settle plate method. Swabs were taken from different sites and equipments and bacterial species were isolated and identified from them. Results: A total of 1410 samples were collected from various sites of Operation theaters and Intensive care units over a period of 6 months in which 960 were surface samples and 450 were air samples. Out of 960 surface samples, 95(9.89%) and out of 450 air samples, 90 (20%) were bacterial positive. Isolated organism was divided into normal flora (CONS, Micrococci), contaminant (bacillus species) and pathogenic organism e.g. Staphylococcus aureus, Acinetobacter spp., Pseudomonas spp etc. Out of those 30 (16.20%) CONS, 50 (27.02%) Micrococci, 75 (40.50%) Bacillus spp, 16 (8.6%) Staphylococcus aureus, 1(0.54%) Acinetobacter spp, 2 (1.08%) Pseudomonas spp, 4 (2.16%) Klebsiella, 7 (3.78%) Escherichia coli were isolated. Conclusions: Strengthening surveillance and laboratory capacity will surely enhance infection prevention and control. Routine sampling is strongly recommended for increasing awareness to identify and control all possible sources and types of infections.